Pendampingan Belajar Matematika di Rumah pada Masa Pandemi Covid 19 - Ningsih, Ningsih; Wondo, Maria Trisna Sero; Mei, Maria Fatima; Seto, Stefania Baptis; Meke, Konstantinus Denny Pareira; Naja, Finsensius Yesekiel; Sa'o, Sofia; Djou, Ana Maria Gadi; Bolak, Aloysius (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2023)
Online learning has become a problem for students and parents since the Covid-19 pandemic. Carrying out tutoring of mathematics for students is an alternative problem-solving done by lecturers in the mathematics education study program, at the University of Flores. Home tutoring activities are carried out at RT 003 Paupire sub-district, Ende Tengah District, every Monday, Wednesday and Friday from 16.00-17.30 WITA. The participants are elementary school students who live in RT 003. Methods of implementation include lectures, question and answer/discussion, assignments, and evaluation methods. Based on the results of observation and evaluation of learning at each meeting and every week it was found that students were motivated in learning and obtained increased learning outcomes.